Penegakan Hukum Terhadap Pelaku Tindak Pidana Pencurian Aliran Arus Listrik Yang Sering Terjadi Di Kayuagung - Kiki Rezvianti; Aprianto; Aan Hendry; Raldo Andika Mandasia (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
The factors causing the crime of theft of electric current in Kayuagung are electrical installation procedure factors, economic factors, environmental factors and weak law enforcement against perpetrators of criminal acts of theft of electric current. The efforts made by PT. PLN (PERSERO) Kayuagung branch regarding the criminal act of theft of electric current by carrying out preventive and repressive efforts. Preventive efforts are efforts made to change a person's negative characteristics into positive ones and can provide knowledge about the dangers of committing electricity theft, while preventive efforts are made to provide a deterrent effect against perpetrators of electric current theft.